Use of Plerixafor for Stem Cell Mobilization in the Setting of Autologous and Allogeneic Stem Cell Transplantations: An Update [Corrigendum] - Bilgin YM (Journal of Blood Medicine, 2022)
Bilgin YM. J Blood Med. 2021;12:403–412. The author wishes to advise of an error in the units of measurement for CD34 concentrations which were shown as 109/L but should have been 106/L throughout the paper. The author apologizes for any inconvenience and advises it does not affect the results of the paper.